ANALYSIS OF TIKTOK PLATFORM UTILIZATION IN BUSINESS MARKETING - Sudiantini, Dian; Nazira, Nawfa Ayu; Sari, Rini Nurmila; Habibah, Siti; fizikri, Bukhori Al (SENTRI: Jurnal Riset Ilmiah, 2024)
An analysis of the use of the TikTok platform in business marketing strategies shows that TikTok is a popular digital marketing platform among the public. The platform offers a wide array of interesting features and an extensive database. TikTok is also a potential place to gain profits in commerce thanks to its rising popularity. The use of TikTok can significantly change human behaviour by collecting and recording various moments to provide a comprehensive picture of an event. TikTok has evolved from an entertainment platform to a strategic tool in business planning, including through effective communication strategies to change human behaviour in a big way. With its rich features and database, TikTok has great potential as an effective business marketing platform in commerce